PERLINDUNGAN HUKUM TERHADAP PEMBERI FIDUSIA DALAM PELAKSANAAN EKSEKUSI JAMINAN FIDUSIA KENDARAAN BERMOTOR RODA EMPAT (Studi Di BCA Multifinance Ringroad Medan) - Fadillah Hanum; Ayu Trisna Dewi (Law Jurnal, 2022)
ABSTRACTThe problems experienced by many financial institutions that provide credit and financing services, namely the transfer of objects fiduciary guarantee by the debtor to a third party. The problem is getting worse complicated, due to the transfer of the object of collateral by the debtor and other parties these three (whether through buying and selling, renting, or otherwise) will happen the intersection of rights between a third party as the ruler of the object and the creditoras the legal owner of the object.The problem raised in this thesis is the implementation of execution fiduciary guarantee object through parate execution due to transfer of collateral object fiduciary by the debtor to a third party. Legal protection for banks BCA multifinance in the execution of the object of fiduciary guarantee against the object of the fiduciary guarantee that has been transferred to a third party. Types of research used in this research is empirical juridical. This research descriptive research. The source of the data in this study was obtained by collect primary data and secondary data. Data collection techniques in This research is a field study (field research). Data analysis to be carried out in this study is a qualitative analysis.The purpose of the legal implications of the debtor is to transfer the object of collateral fiduciary to a third party in a financing agreement, resulting in the fiduciary agreement becomes null because in the fiduciary agreement the object Fiduciary guarantee is one of the important elements of a fiduciary agreement there is a legal consequence if an object of the fiduciary guarantee is lose their property rights.Legal protection for creditors in a fiduciary guarantee agreement born from the making of a deed of imposition of a fiduciary guarantee made notarial, and continues to be confirmed by registration with the Fiduciary Registration Officein order to obtain a fiduciary certificate. By registering the guarantee fiduciary, then the principle of publicity is fulfilled this is a guarantee of legal certainty to creditors in returning their receivables from the debtor.Keywords: Legal Protection, Execution, Fiduciary Guarantee, Vehicle Four Wheel Motor